Особые экономические зоны регионального уровня: специфика создания и функционирования (Путеводитель предпринимателя)
Special economic zones (SEZs) as an instrument of realization regional zoning conception’s in the system of regional economic relations are conducted in the article. Development’s specific of these zones in russian practice is examined, also possibility of creation of Special economic zones at regional level in Russian Federation is analyzed.